2002
DOI: 10.1002/1615-9861(200203)2:3<241::aid-prot241>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional proteomics using chromophore- assisted laser inactivation

Abstract: Proteins are the molecules that fulfil most cellular functions and represent over 90% of drug targets in the market. Chromophore-assisted laser inactivation (CALI) provides a timely and locally restricted protein inactivation and has proven to specifically destroy protein function using dye-coupled ligands and laser irradiation. CALI involves the generation of short-lived radicals thus limiting the radius of covalent modifications to spatially restricted sites on the target molecule. A transient functional ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…It has previously been shown that FALI of Fas or caspase-3 can block apoptosis as measured by a viability assay (22). In this study, we sought to adapt FALI to a miniaturized format that would lend itself readily to high-throughput functional proteomic analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that FALI of Fas or caspase-3 can block apoptosis as measured by a viability assay (22). In this study, we sought to adapt FALI to a miniaturized format that would lend itself readily to high-throughput functional proteomic analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, by not loading antibody into cells, it is possible to exclusively examine the function of the extracellular compartment of a targeted protein (19,22).…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of these approaches is the ability to inactivate a specific site in a protein in a time-dependent and localization-restricted manner, as with chromophore-assisted laser inactivation (CALI). Such inactivation allows assessment of the disease relevance of the site and provides a means to revert a cellular phenotype to a more normal state 49 (Fig. 4).…”
Section: Disease-related Functional Proteomicsmentioning
confidence: 99%
“…The commonly used fluorophore fluorescein was highly efficient in loss of b-galactosidase activity in CALI while green fluorescent protein (GFP) was about the same as Malachite green. Fluorophore-assisted light inactivation (FALI) was developed [10], which took advantage of the greater efficiency of fluorescein to permit use of non-laser light sources (such as a slide projector) to simultaneously irradiate many samples in multi-well plates [11], thus providing the potential for high-throughput CALI [12,13].…”
Section: Family Of Cali-based Technologiesmentioning
confidence: 99%